OP0217 Adjudication of Infections in The Pharmacovigilance in Juvenile Idiopathic Arthritis Patients (Pharmachild) Treated with Biologic Agents and/or Methotrexate. (15th July 2016) - Swart, J.; Giancane, G.; Bovis, F.; Castagnola, E.; Groll, A.; Horneff, G.; Huppertz, H.-I.; Lovell, D.; Wolfs, T.; Hofer, M.; Alekseeva, E.; Panaviene, V.; et al.
Abstract : Background: The Pharmachild study is aimed at observing children with JIA undergoing treatment primarily with biologics±methotrexate (MTX). It is conducted by the participating centres of over 60 countries belonging to PRINTO and PReS. Objectives: Primary endpoint of the study is safety in JIA patients undergoing immunosuppressive therapy. A preliminary analysis of infections has been performed by an independent Safety Ajudication Committee of 6 experts (3 pediatric rheumatologists and 3 pediatric infectious disease specialists). Methods: The centres were asked to report all infections encountered by the patients followed for JIA. Data were checked by PRINTO and the medical monitor based on MedDRA dictionary. Upon completion of these steps, all eligible cases for adjudication, represented by serious/severe/very severe infections, were submitted to the expert Committee. The experts were asked to answer 6 questions. The events with consensus of at least 4/6 experts on more than 3/6 questions were considered. An additional analysis was performed on opportunistic infections, with referral to the recommendations by Withrop et al. 1, and on the correlation between infections and 3 treatment phases: MTX only, first biologic±MTX and at least 2 sequential biologics±MTX after failure of the first biologic. Results: 7817 patients were enrolled in Pharmachild at the time of preliminary analysis, with 27% of total safety events reported as infections. 360 events were submitted to the Safety Adjudication Committee. 94 infections (26.1%) achieved maximum consensus among the experts (6/6 questions), 237 (65.8%) consensus on 4/6 or 5/6 questions, the remaining events were discarded. 330 infections were finally retained for the analysis, mostly represented by serious infections of moderate/severe intensity. With regard to the other questions, 74.2% infections were adjudicated as common, appropriately treated, with no clear correlation to the immunosuppressive therapy. The experts achieved consensus on 18 infections adjudicated as opportunistic. Referring to the list of opportunistic infections provided by Winthrop et al. 1, we identified 89/330 (27%) opportunistic infections, mostly represented by EBV and herpes zoster infections. 98.8% of events were not recoded. A doubled risk of infections was found in the group of patients who were started on their first biologic±MTX or who had been treated with at least 2 sequential biologics±MTX (1.3 and 1.9 infectious events per 100 py, respectively), compared to the MTX only group (0.8 infectious events per 100 py). The same was found for serious and opportunistic infections. Conclusions: Our preliminary analysis showed a significant number of infections in JIA patients on immunosuppressive therapy, with one third classified as opportunistic infection. The introduction of biologics in therapy increased the risk of opportunistic and serious infection. References: Winthrop et al. Ann Rheum Dis. 2015;74:2107–16. Disclosure of Interest: None declared